Participatory health impact assessment - Boelee, Eline; Laamrani, Hammou (2009)
This tool contains guidelines intended to reduce the health risks and increase the health benefits from small reservoirs. Guidelines are structured in a step-wise manner, beginning with the identification of relevant health issues and concluding with small reservoir design and operation for improved human health. The guidelines focus on: major water-related diseases associated with small reservoirs in Africa, the added value of community participation in health impact assessment, opportunities to mitigate risks and improve human health through better planning and operation of small reservoirs, and improved planning, design, and management options.